A motivational Self-System Model Construction for Persian Language Learners as L2 - Esmaeil Sadipour; Zohreh Molaee; Amir Reza Vakilifard (پژوهش در نظام‌های آموزشی, 2017)
The main purpose of this research was to develop a motivational model for Persian language learners as a second language (L2). To do this, a correlation research design has been selected with a simple random sampling method and sample size of n=242 among all of Persian instruction center of Imam Khomeini, International University language learners on first semester of 2016-2017. The applied instrument was an author made, Persian Language Motivational Self-System questionnaire in four items of ought-to Self, Persian language, Self-Efficacy, Persian Learning Experience & Motivated Learning Behavior. The instrument reliability here, Cronbach’s alpha   was 0.90 & it’s content validity mean was, CVR=0.95 which had been estimated with confirmatory factor analysis method. The results of regression analysis affirmed a significant effect of learning experience on self-efficacy, and also effect of learning experience on motivated learning behavior, Ought-to self on motivated behavior and self-efficacy on motivated behavior. However, the ought-to self, had no significant effect on self-efficacy. The most powerful effect has been reported in the case of learning experience and secondly self-efficacy on   motivated behavior. The indirect effect of ought-to self on motivated behavior via self-efficacy was not significant, the indirect effect of learning experience on motivated behavior via self-efficacy was significant.